Conditions for inclusive education from the viewpoint of headmasters - Janez Kovač; Tanja Ščuka; Branka Čagran (University of Maribor Press, 2017)
The paper presents conditions for inclusive education as perceived by headmaster in Slovenian primary schools. In the theoretical part, we focused on key elements of inclusive schools, i.e. headmasters, teachers and parents of children with special needs. In conclusion, we briefly highlight some theoretical propositions in relation to additional professional support in primary schools. In the empirical part of the paper, we present the results of an online survey conducted among headmasters in Slovenian primary schools. The aim of the survey was, among other things, to find how headmasters perceive conditions for inclusive education - those relating to headmasters themselves, to teachers/professional staff working with students with special needs, and those relating to school as a whole. Here, we also paid our attention to differences regarding the number of children with special needs who are included in regular program with adjusted implementation and additional professional assistance. The obtained results provide an opportunity for assessment of current situation, and for further consideration concerning the development of inclusive education in Slovenia in the future.